If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -3x = 2x + 9 Reorder the terms: m + -3x = 9 + 2x Solving m + -3x = 9 + 2x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3x' to each side of the equation. m + -3x + 3x = 9 + 2x + 3x Combine like terms: -3x + 3x = 0 m + 0 = 9 + 2x + 3x m = 9 + 2x + 3x Combine like terms: 2x + 3x = 5x m = 9 + 5x Simplifying m = 9 + 5x
| -44=-6x-3x+10 | | -15t^2+150t-315=0 | | sr-t=us+t | | 18x^2+7X-8=0 | | 1.5-0.04X=-0.9 | | 11(10)+7= | | 238=21-v | | 2x(2x)-4= | | x(9x+18)=4x^2-6x+5 | | -2(3x+5)-4(3-x)=12 | | [2-3x]+2=9 | | 9y-2y=21 | | 2r+14=28 | | 2n-6+36=15 | | -(4x-5y+2)= | | q+13=16q+0 | | 3x^2+7=115 | | 3x^2+7x-115=0 | | 6(20)+5= | | 0.4(2x-0.8)=1/7(4.9x+7) | | 65q+13=2q+0 | | 2(4r+6)=2/5(12r+18) | | 3000/x=550 | | 5m-3n+2m-n= | | -49=v+42-5v | | 2d+18=16-(d+7) | | 0.50x+0.75y=42 | | 3=93-2 | | f(x) = 7 + x52 | | 5b+45=6b+9 | | 72+4-12d=3 | | 7a-2(-1)=17 |